Lamivudine Inhibits the Replication of ALV-J Associated Acutely Transforming Virus and its Helper Virus and Tumor Growth In vitro and In vivo - Wang, Yixin; Xu, Shuzhen; Li, Sifei; Su, Hongqin; Chang, Shuang; Li, Yang; Sun, Xiaolong; Zhao, Peng; Cui, Zhizhong (Frontiers in Microbiology, 2015)
To study the antiviral effects of lamivudine on avian leukosis virus subgroup J (ALV-J) and its inhibitory effect on the growth of fibrosarcomas caused by acute transforming ALV, a series of experiments were performed in chicken embryo fibroblast cultures and 1-day-old chickens inoculated with an acutely transforming viral stock Fu-J (SDAU1005). This stock was prepared from an acutely fibrosarcoma of field cases in chicken farms and contained both the replication-defective virus Fu-J carrying v-fps oncogene and its helper virus ALV-J strain SDAU1005. The results from 3 different assays in cell cultures demonstrated the significant inhibitory effect of lamivudine on the replication of both SDAU1005 and Fu-J viruses. Furthermore, the effect was dose dependent in the concentration range of 1–4 μg/ml. In chicken experiments, lamivudine could decrease the viral loads of SDAU1005 and Fu-J in the plasma of inoculated chickens, delay the appearance of acute sarcomas, and decrease chicken mortality in the early stage. This model may be used to directly evaluate the inhibitory effects of lamivudine on such tumors and to understand the relationship between the replication-defective virus and its helper virus while also assessing tumor processes.